Rancangan Sistem Prediksi Harga Saham dengan Menggunakan Metode LSTM dan ARMA klasik - Caesar Calendo Sumarga; Dyah Erny Herwindiati; Janson Hendryli (Fakultas Teknologi Informasi Universitas Tarumanagara, 2023)
Stocks are one of the types of assets that are currently popular with the wider community, just like gold and all other types of assets, the value of stocks tends to move up and down over time, therefore stock investors invest in stocks to achieve the desired profit (capital gain), Due to the movement of stocks that go up and down over time, it is difficult for investors to determine when to buy or sell stocks, therefore this study was conducted to compare the multivariate Long-Short Term Memory (LSTM) method, and the classic ARMA, then see which is suitable in forecasting stock prices, the comparison is seen from the results of the error evaluation metrics of the two methods.